Mapping of restrictive factors of land in the hydrographic basin of the middle section of the Paraíba River - Francisco, Paulo Roberto Megna; Silva, Viviane Farias; Santos, Djail; Ribeiro, George do Nascimento; Ayres, Gypson Dutra Junqueira (Revista Agrogeoambiental, 2022)
This work aimed to identify and map the pedological restrictions of the lands in the middle course of the Paraíba River. For this, GIS SPRING, digital soil map, and the Agricultural Zoning of the State of Paraíba information were used. From these, pedological data were extracted to classify the soils based on salinity/sodicity, effective depth, stoniness, fertility, erosion, drainage, and texture. Data were interpreted and classified according to soil-restricting factors (null, light, moderate, strong, very strong, and extremely strong). It was observed that the most common land use restriction factors in the strong class were texture, effective depth, and stoniness; in the moderate class, erodibility, slope, and fertility; in the light class, slope; and in the null class, salinity and drainage.